Noospheric Vocation of Greater Eurasia in the XXI Century - A. I. Subetto; V. A. Shamakhov (Евразийская интеграция: экономика, право, политика, 2021)
The article reveals the theoretical position on the noospheric vocation of “Greater Eurasia” in the 21st century. Opposition to the “Big West” as a global imperialism system of the world financial capitalocracy on the part of Greater Eurasia acquires a noospheric and socialist “dimension” in the 21st century. Russia is called upon to head the Noosphere Breakthrough of humanity in the XXI century, as a Eurasian civilization, occupying an important place in the Greater Eurasia’s structure, and as the birthplace of the socialism first appearance in the world and the doctrine of the Biosphere transition into the Noosphere by V. I. Vernadsky, and as a center of stability and instability in the world. Greater Eurasia is called upon to become the “locomotive” of noospheresocialist transformations of the human existence foundations. The alternative to this is the death of mankind, which is market-capitalistic for reasons and ecological for foundations.